Mitochondria as a target for novel chemotherapeutic agents based on phenolic acids - Teresa L. Serafim (2010)
Every day, new molecules with antineoplastic potential are discovered. Unfortunately, most of these molecules lack cell-type specificity, and are unable to kill tumor cells any more efficiently than normal cells. Also, a high number of those molecules are very toxic. In order to design more effective chemotherapeutic drugs, it is important to understand the interaction between novel molecules and biological systems. Certain cellular components are particularly relevant in the context of specific targeting and mechanisms of action. Mitochondria are not only the major source of cell energy but are also important in the control of processes that culminate in apoptotic cell death. Particular aspects of mitochondrial physiology (e.g. the negative transmembrane electric potential) facilitate selective targeting by anti-cancer molecules. Such mitochondria-specific drugs are referred to as 'mitocans'. Among potential mitocans, phenolic acids are attractive candidates. Plant-derived phenolic compounds are widely consumed in a normal diet, especially in fruits and vegetables. Besides their antioxidant properties, phenolic acids have been reported to display antiproliferative activity by promoting selective induction of tumor cell apoptosis. In some cases, the molecule acts by triggering the mitochondrial pathway for apoptosis. Here we review the potential role of several phenolic acids and derivatives as anti-cancer agents, highlighting the role of mitochondria as a primary subcellular target for this class of compounds. The present review intends to raise awareness for this promising direction of research.